Bathymetric Measurements of a Retention Reservoir using Integrated Hydrographic and Photogrammetric Techniques - Błażej Mach; Michał Skrzypek (Communications - Scientific letters of the University of Zilina, 2022)
The purpose of this paper was to determine the usability of unmanned hydrographic drones and photogrammetric techniques during the conduct of work, the results of which are potentially to serve as navigational materials in areas that, due to their characteristics, make it impossible to carry out research using crew vessels and direct shoreline determination. In order to prepare and carry out the measurement campaign with the greatest possible accuracy and safety, the authors of the article decided to determine the shoreline of the analyzed reservoir using photogrammetric methods. The use of satellite images allowed the border between land and water to be identified as precisely as possible, which had a direct impact on the accuracy of relating depth data to their location on Earth’s globe. Use of unmanned vessels and orthophotos can find practical application when navigating vessels during maneuvers required high precision.